Utilizing Microbial Electrochemical Methods to Enhance Lycopene Production in Rhodopseudomonas palustris - Ningxin Huang; Zhengxiao Wang; Xiao Xiao; Te’er Gai; Dongyue Zhao; Lu Liu; Wei Wu (Foods)
Utilizing Rhodopseudomonas palustris (R. pal), this study constructed a dual-chamber microbial electrosynthesis system, based on microbial electrolysis cells, that was capable of producing lycopene. Cultivation within the electrosynthesis chamber yielded a lycopene concentration of 282.3722 mg/L when the optical density (OD) reached 0.6, which was four times greater than that produced by original strains. The mutant strain showed significantly higher levels of extracted riboflavin compared to the wild-type strain, and the riboflavin content of the mutant strain was 61.081 mg/L, which was more than 10 times that of the original strain. Furthermore, sequencing and analyses were performed on the mutant strains observed during the experiment. The results indicated differences in antibiotic resistance genes, carbohydrate metabolism-related genes, and the frequencies of functional genes between the mutant and original strains. The mutant strain displayed potential advantages in specific antibiotic resistance and carbohydrate degradation capabilities, likely attributable to its adaptation to electrogenic growth conditions. Moreover, the mutant strain demonstrated an enrichment of gene frequencies associated with transcriptional regulation, signal transduction, and amino acid metabolism, suggesting a complex genetic adaptation to electrogenic environments. This study presents a novel approach for the efficient and energy-conserving production of lycopene while also providing deeper insights into the genetic basis of electro-resistance genes.